The Effect of AI Application Use on Improving Students' Narrative Writing Skills - Safar, Muh. (MSJ : Majority Science Journal, 2025)
This study examines the influence of AI application use on students’ narrative text writing skills and investigates the mediating role of writing self efficacy within a quantitative PLS SEM framework. AI enhanced writing environments have increasingly shaped literacy practices in digital era classrooms, providing automated feedback, structural guidance and interactive support that assist students in managing the cognitive complexity of narrative composition. Data were collected from junior secondary students who used AI based writing tools during classroom activities. The findings show that AI application use significantly improves narrative writing skills by enhancing linguistic accuracy, narrative coherence and idea development. The results also reveal that writing self efficacy partially mediates the relationship between AI application use and narrative writing skills. Students who frequently engaged with AI feedback cycles demonstrated higher confidence in their writing abilities, which subsequently contributed to improved narrative performance. The structural model highlights the interconnected cognitive and motivational pathways through which AI tools operate, suggesting that effective integration of AI based platforms can strengthen both competence and learner belief. The study concludes that AI applications should be systematically integrated into narrative writing instruction through structured drafting cycles and guided feedback checkpoints. Strengthening digital literacy and fostering writing self efficacy are essential to maximizing learning outcomes. Future research is encouraged to explore long term effects of AI supported writing instruction and variations across learner profiles